Analisis Passing Kontrol Futsal Pada Pemain Himajas Universitas Dehasen Bengkulu - Alfiqri, A Chaltren Surya; Ritanza, Febra; Syaputra, Roni (Educative Sportive, 2024)
This study aims to describe futsal control passing in Himajas players at Dehasen University Bengkulu. This type of research is Quantitative Descriptive with the Population used in this study are all students who take part in extracurricular activities. The samples taken in this study were 15 students with sampling through the Total Sampling technique. The results of the study on the analysis of Passing Control Futsal Players Himajas Dehasen University Bengkulu is in the medium category with a frequency of 8 players with a percentage of 53% of the total 15 players, most of them show a consistent ability to control the ball and overcome opponent pressure. However, there were variations in skill levels between players, with some showing higher skill levels than others. Himajas Dehasen futsal passing control obtained data that the highest score was 32 and the lowest score was 22. From the data analysis, an average price (Mean) of 28.1 was obtained. There are five categories, namely, excellent, good, moderate, less and very less on the detailed classification of values, namely there are 3 people or (20%) are on a score> 32 people or (13%) are on a score of 29-31, 2 people or (53%) are on a score of 26-28, 8 people or (13%) are on a score of 22-25, 2 people or (0%) are on a score < 21.